Learning from linguistics: structuring our sentences sensitively. Issue 1 (2nd January 2016) - Carr, Sarah
Abstract: It is important not to use language in a way that excludes certain people or groups. 'Readability' (or 'understandability', in the case of spoken language) is a common concept in the plain-language ﬁeld. It applies to choosing both vocabulary and syntax (sentence structure). Having looked in a previous article at techniques to help bereavement-support workers use understandable words and phrases when communicating with clients, this article examines basic techniques to improve sentence clarity. These include avoiding long sentences and paragraphs; using active-voice verbs; and ensuring good grammar, spelling and punctuation. It also describes how to check the readability of your text using a feature built into Microsoft Word.